2023
DOI: 10.1002/smll.202303366
|View full text |Cite
|
Sign up to set email alerts
|

Control of Halogen Atom in Inorganic Metal‐Halide Perovskites Enables Large Piezoelectricity for Electromechanical Energy Generation

Abstract: Regulating the strain of inorganic perovskites has emerged as a critical approach to control their electronic and optical properties. Here, an alternative strategy to further control the piezoelectric properties by substituting the halogen atom (I/Br) in the CsPbX3 perovskite (X = Cl, Br) structure is adopted. A series of piezoelectric materials with excellent piezoelectric coefficients (d33) are unveiled. Iodine‐incorporated CsPbBr2I demonstrates the record intrinsic piezoelectric response (d33 ≈47 pC N−1) am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…The origin of d 33 enhancement is mainly ascribed to the increased BX 6 octahedral distortion in the lattice and the off-centring of the B atoms [58,60,62]. Chen et al [45] and Khan et al [61] reported that applying a poling voltage of 3 V and 40 V during the PFM measurement was enough to observe the domain switching during the PFM measurement.…”
Section: Coefficients Of Halide Perovskite Thin Filmsmentioning
confidence: 99%
See 3 more Smart Citations
“…The origin of d 33 enhancement is mainly ascribed to the increased BX 6 octahedral distortion in the lattice and the off-centring of the B atoms [58,60,62]. Chen et al [45] and Khan et al [61] reported that applying a poling voltage of 3 V and 40 V during the PFM measurement was enough to observe the domain switching during the PFM measurement.…”
Section: Coefficients Of Halide Perovskite Thin Filmsmentioning
confidence: 99%
“…The grain size effect on the piezoelectric properties of halide perovskites has not been exploited in detail so far. However, recently, Khan et al [61] reported that a large grain size (~200 nm) is important for enhanced d 33 values, and the authors attribute this to the easier displacement of domain walls in larger grains. The grain size information is not reported for all the halide perovskites listed in Tables 1 and 2.…”
Section: Coefficients Of Halide Perovskite Thin Filmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since these properties and functions are directly related to ferroelectric phase transitions, controlling and tuning the phase transition temperature or Curie temperature ( T C ) is the key to optimizing the performances of ferroelectric materials for various applications 31 . Common approaches to tuning the T C mainly focus on controlling the chemical compositions, including H/D isotope substitution 32 35 , H/F substitution 36 , 37 , metal/cation/anion doping 24 , 38 , etc 39 . These approaches can alter the local intermolecular interactions and structural symmetries of the crystals and thereby affect the T C 40 .…”
Section: Introductionmentioning
confidence: 99%